CB[10]-driven self-assembly of a homotrimer from a symmetric organic dye: tunable multicolor fluorescence and higher solid-state stability than that of a CB[8]-included homodimer. Issue 22 (6th October 2022) - Zhang, Le-Ping; Liu, Chuan-Zhi; Liu, Ming; Lu, Shuai; Yu, Shang-Bo; Qi, Qiao-Yan; Yang, Guan-Yu; Li, Xiaopeng; Yang, Bo; Li, Zhan-Ting
Abstract : A symmetric organic dye can form a highly stable homotrimer in the cavity of CB[10], which exhibits unique multicolour fluorescence different from that of the single molecule or its dimer. Abstract : Although a large number of cucurbit[8]uril (CB[8]) inclusion-based homodimers have been reported and found wide applications in the construction of various advanced materials and supramolecular architectures, the self-assembly of homotrimers through the inclusion of larger macrocycles has been a challenge. Here we describe that cucurbit[10]uril (CB[10]) can induce a benzothiadiazole-incorporated, structurally symmetric conjugated molecule (G1 ) to trimerize in its cavity. The new homotrimer exhibits tunable multicolor fluorescence in both water and the solid state. 1 H NMR, UV-vis absorption and cell imaging experiments show that in aqueous solution this homotrimer possesses high stability comparable with that of a CB[8] inclusion-induced homodimer. Solid state (transient) fluorescence spectroscopic experiments reveal that the homotrimer is also stable enough to maintain its stacked structure in the cavity of CB[10], while the CB[8]-induced homodimer is less stable and decomposes. The work provides a new approach for the development of advanced supramolecular architectures that exhibit otherwise inaccessible, high stability and property tunability through the inclusion of large macrocycles.